Fare's fair? Concessionary travel policy and social justice. (29th June 2016) - Houston, Donald; Tilleyed, Sara
Abstract : This paper argues that transport has an important influence on individuals' welfare and therefore transport policy can be readily analysed from social justice and welfare policy perspectives – yet only rarely ever is. The paper develops a justice framework in which to assess the 'fairness' of the eligibility criteria used in concessionary fare policies – specifically the justice principles of need, desert, equality, option choices and affordability. The paper examines a concessionary bus fares policy from a social justice perspective, including an empirical assessment of who in practice benefits most from it and how these findings measure against justice principles.